The Influence of Live Streaming Features and Ease of Use on Purchase Intention for Muslim Fashion Products on Shopee Mediated by Consumer Trust - Muhriza, Nurul; Purwo Saputro, Edy; Sholahuddin, Muhammad; Kussudyarsana, Kussudyarsana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This study focuses on analyzing the impact of live streaming features and ease of use on purchase intention for Muslim fashion products on Shopee, with consumer trust as a mediator. The research uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to 150 respondents who are active Shopee users in Sukoharjo Regency. Data analysis is performed using SmartPLS 3 to test the structural model and relationships between variables. The results show that live streaming and ease of use significantly affect consumer trust. Live streaming features also significantly affect purchase intention, while ease of use does not. Consumer trust is proven to mediate the relationship between live streaming features and purchase intention, as well as between ease of use and purchase intention. This research provides important implications for e-commerce industry practitioners, especially in marketing strategies for Muslim fashion products through the Shopee platform, highlighting the importance of live streaming features and building consumer trust to enhance purchase intention.